Analysis of Fraud in Cybercrime Perspective - Erwinsyahbana, Tengku; Rambey, Guntur (International Asia Of Law and Money Laundering (IAML), 2025)
The development of digital technology has transformed the landscape of conventional fraud crimes into more complex and sophisticated cybercrime crimes. This study analyzes the characteristics, modus operandi, legal arrangements, and obstacles to law enforcement against fraud in the perspective of cybercrime in Indonesia. Using a normative juridical approach, this study examines primary and secondary legal materials relevant to digital technology-based fraud crimes. The results showed that cyber fraud has distinctive characteristics such as the nature without geographical boundaries, the anonymity of the perpetrators, and the use of information technology as the main means of crime. The growing Modus operandi includes phishing, social engineering, electronic transaction fraud, digital identity theft, to cryptocurrency investment fraud. Regulation of Indonesian criminal law through Article 378 of the Criminal Code and Law No. 19 of 2016 on information and electronic transactions has provided a juridical foundation, but there is still a gap between the dynamics of technology and regulatory readiness. The main obstacles faced include the limited competence of the apparatus in digital forensics, the lack of valid electronic evidence, and the complexity of handling cross-jurisdictional cases. Optimizing handling requires increasing the capacity of law enforcement officers, harmonizing regulations, strengthening international cooperation, and improving digital literacy in a comprehensive and sustainable manner.